TUMOR NECROSIS FACTOR α, INTERLEUKIN 1β AND DATAS OF ERYTHROPOESIS IN PATIENTS WITH CHRONIC HEART FAILURE OF ISCHEMIC GENESIS AND ANEMIA - Rynchak, P.I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
120 patients with CHF and anemia were exemained. CHF of II FC was found in 49 patients, III FC – in 42 and IV FC in 29 patients. All patients had standart treatment. The level of hemoglobin, MKV, MCH, MCHC, hematocrite, serum iron, ferritine, erythropoetin, tumor necrosis factor α, interleukin 1β. It was found that the level of hemoglobin and serum iron in patients with CHF of ischemic genesis was decreased and it has direct relation to increased level of proinflammatory cytokins, which increases in parallel to incerasement of erythropoetin, which reflects cytokininducted appearance of anemia in patients with CHF as a result of erythropoesis inhibition.